The Peacock Spiders (Araneae: Salticidae: Maratus) of the Queensland Museum, including six new species - Baehr, Barbara C.; Whyte, Robert (Zootaxa, 2016)
Six new species of the peacock spider genus Maratus Karsch, 1878 are described from Australia: M. eliasi sp. nov., M. julianneae sp. nov., M. licunxini sp. nov., M. michaelorum sp. nov. and M. ottoi sp. nov. from Queensland, and M. kiwirrkurra sp. nov. from Western  Australia. Five species groups are further documented within the genus and new records, detailed SEM and automontage images are provided for six previously described species: M. anomalus Karsch, 1878, M. chrysomelas (Simon, 1909), M. digitatus Otto & Hill, 2012, M. pavonis (Dunn, 1947), M. speciosus (O.P.-Cambridge, 1874) and M. volans (O.P.-Cambridge, 1874).